Regulatory B Cells Are Decreased and Functionally Impaired in Myasthenia Gravis Patients - Lin, Ye; Chang, Ting; Lin, Jiaji; Sun, Chenjing; Wei, Chao; Zhao, Jiao; Liu, Rui; Yang, Kun; Li, Zhuyi (Frontiers in Neurology, 2022)
Myasthenia gravis (MG) is an autoimmune disease mediated by B cells secreting autoantibodies. Regulatory B (Breg) cells confirmed to have an immunosuppressive function play an important role in many autoimmune diseases. However, what about the changes in Breg cells in the thymus and peripheral blood of MG patients? The changes in the proportion of Breg cells in the peripheral blood of 41 MG patients without any drug treatment and 30 healthy controls were detected by flow cytometry. We found that the proportions of CD19+ IL-10+ cells and CD19+CD24hiCD38hi cell subsets in MG patients were significantly lower than those in healthy controls. Then, we detected the proportion of CD19+ IL-10+ cells in thymus tissues of 10 healthy children, 4 healthy adults and 12 MG patients by flow cytometry. However, the percentage of CD19+ IL-10+ cells was highest in healthy children (approximately 8%), followed by healthy adults (approximately 3%), and was lowest in MG patients (approximately 0.5%). CD19+CD24hiCD38hi B cells exerted immunosuppressive functions in healthy people but were refractory in MG patients. Moreover, p-STAT3 downstream of CD40 may be impaired in CD24hiCD38hi B cells from the peripheral blood of MG patients.